The adventures of Nanny Piggins - Spratt, R. A. (Little, Brown, 2012)
When Mr. Green, a stingy widower with three children he cannot be bothered with, decides to find a nanny for his children, he winds up hiring a glamorous ex-circus pig who knows nothing about children but a lot about chocolate.